Cancer care pathways across seven countries in Europe: What are the current obstacles? And how can artificial intelligence help? - Hesso, Iman; Kayyali, Reem; Zacharias, Lithin; Charalambous, Andreas; Lavdaniti, Maria; Stalika, Evangelia; Ajami, Tarek; Acampa, Wanda; Boban, Jasmina; Gebara, Shereen Nabhani (My University, 2024)
Cancer poses significant challenges for healthcare professionals across the disease pathway including cancer imaging. This study constitutes part of the user requirement definition of INCISIVE EU project. The project has been designed to explore the full potential of artificial intelligence (AI)-based technologies in cancer imaging to streamline diagnosis and management. The study aimed to map cancer care pathways (breast, prostate, colorectal and lung cancers) across INCISIVE partner countries, and identify bottle necks within these pathways.
Keywords: Treatment; Cancer; Cancer care; Care pathway; Comparative analysis; Delay; Diagnosis